Acute left ventricular insufficiency in a Burkitt Lymphoma patient with myocardial involvement and extensive local tumor cell lysis: a case report - Maren Schmiester; Eva Tranter; Alessandro Lorusso; Florian Blaschke; Dominik Geisel; Lars Bullinger; Frederik Damm; Il-Kang Na (BMC Cardiovascular Disorders, 2022)
Abstract Background Burkitt lymphoma (BL) is a rare disease with the sporadic variant accounting for less than 1% of adult non-Hodgkin lymphomas. BL usually presents with an abdominal bulk, but extranodal disease affecting the bone marrow and central nervous system is common. Cardiac manifestations, however, are exceedingly rare, with less than 30 cases reported in the literature. Case presentation We report on a 54-year-old male patient with a six week-long history of paranasal sinus swelling, fatigue and dyspnea on exertion. Stage IV sporadic BL with extensive lymphonodal and cardiovascular involvement was diagnosed. Manifestations included supra- and infradiaphragmatic lymphadenopathy as well as infiltration of the aortic root, the pericardium, the right atrium and the right ventricle. EBV-reactivation was detected, which is uncommon in the sporadic subtype. After initial full-dose chemotherapy with very good BL control, the patient developed acute, but fully reversible cardiac insufficiency. Myocardial lymphoma involvement receded completely during the following two therapy cycles, while cardiac function periodically deteriorated shortly after chemotherapy administration and quickly recovered thereafter. Interestingly, the decline in cardiac function lessened with decreasing myocardial lymphoma manifestation. Once the cardiovascular BL infiltration was resolved, cardiac function remained stable throughout further treatment. Following seven cycles of chemotherapy and mediastinal radiation, the patient is now in continued complete remission. Conclusions Although rare, cardiac involvement in BL can quickly become life-threatening due to rapid lymphoma doubling time and should therefore be considered at initial diagnosis. This case suggests an association between myocardial infiltration, chemotherapy associated tumor cell lysis and transient deterioration of cardiac function until the damage caused by the underlying lymphoma could be restored. While additional studies are needed to further elucidate the mechanisms of acute cardiac insufficiency due to lymphoma lysis in the infiltrated structures, prompt BL control and full recovery of the patient supports courageous treatment start despite extensive cardiovascular involvement.